Radiologically isolated syndrome and clinically isolated syndrome. (January 2017) - Niino, Masaaki; Miyazaki, Yusei
Abstract: Magnetic resonance imaging has improved the diagnosis and evaluation of disease activity in multiple sclerosis (MS), and its widespread use has contributed to creating the concept of radiologically isolated syndrome (RIS) to describe patients without symptoms of MS whose magnetic resonance imaging findings suggest they might be at risk of future demyelinating events. Indeed, using the revised McDonald criteria now allows some patients who would have been diagnosed with clinically isolated syndrome (CIS) in the era of Poser criteria to be diagnosed as having MS before a second episode. The present review discusses the current concepts of RIS and CIS, and the risk factors for conversion from these conditions to MS. Clinical trials involving participants with CIS at high risk of developing clinically definite MS have shown that disease‐modifying drugs significantly suppressed the conversion from CIS to MS, and that early treatment with these drugs could improve future disease prognosis in patients who subsequently developed MS. When a patient presents with RIS or CIS, the primary concern for the physician and patient should be the probability of conversion to MS, and the patient should be followed up taking into consideration the risk factors for conversion from RIS or CIS to MS.